2008
DOI: 10.2169/internalmedicine.47.0512
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Japan Stroke Scale -Depression Scale- (JSS-D) for the Diagnosis of Post-stroke Depression

Abstract: Background Post-stroke depression (PSD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Using a score of 2.4, which was identified by a validation study, 14 as the optimal cut-off point for identifying probable depression among patients after acute stroke, the frequency of probable clinical depression in the current sample was 16.3% in males (n=43) and 17.8% in females (n=28) ( P >0.05). Overall, the mean JSS-D score was 1.53±1.64 for males and 1.77±2.24 for females ( P >0.05).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Using a score of 2.4, which was identified by a validation study, 14 as the optimal cut-off point for identifying probable depression among patients after acute stroke, the frequency of probable clinical depression in the current sample was 16.3% in males (n=43) and 17.8% in females (n=28) ( P >0.05). Overall, the mean JSS-D score was 1.53±1.64 for males and 1.77±2.24 for females ( P >0.05).…”
Section: Resultsmentioning
confidence: 94%
“…The Japan Stroke Scale (Depression Scale) (JSS-D), which was developed by the Japan Stroke Society, was administered to all participants to measure their depressive status. 14 JSS-D is a seven-item (mood, feelings of guilt, interest, apathy, anxiety, sleeplessness, and expression) objective measure in which three choices are given for each item. The total score denoting the degree of depression was calculated according to the proper weight of each choice.…”
Section: Methodsmentioning
confidence: 99%
“…The present study also demonstrated an association of depressive symptoms measured by JSS-D with PCS, MCS and all subscales, where all the correlation coefficients were higher than 0.2 and this finding was consistent with previous reports. Various scales have been used for assessment of severity of depression; the present study employed the JSS-D, developed by the Japan Stroke Society, the scores of which have been reported to correlate with the scores on the Hamilton Depression Scale [20,43]. …”
Section: Discussionmentioning
confidence: 99%
“…The Japan Stroke Scale (Depression Scale) (JSS-D), which was developed by the Japan Stroke Society, was administered to all participants to measure their depressive status [ 17 ]. The JSS-D is a 7-item (i.e., mood, guilt feelings, interest, apathy, anxiety, sleeplessness, and expression) objective measurement, in which three choices are given for each item.…”
Section: Methodsmentioning
confidence: 99%
“…Based on ROC curve analysis of JSS-D, probable PSD was defined as a score of 2.4 or higher. The sensitivity and specificity of this cut-off score were 0.950 and 0.988, respectively [ 17 ]. In this study, JSS-D data were collected on the tenth day of hospitalization to assess depressive symptoms in acute post-stroke phase (≤1 month).…”
Section: Methodsmentioning
confidence: 99%